2022
DOI: 10.3390/children9081248
|View full text |Cite
|
Sign up to set email alerts
|

The Study of Nutrient Intake and Adolescent Girls’ Quality of Life in a Rural Area of Indonesia

Abstract: An inadequate nutrient intake correlates with malnutrition, a problem affecting many adolescents worldwide. Nutrient intake is associated with quality of life (QoL). Our study analyzed the relationship between nutrient intake and adolescents’ QoL. We conducted a cross-sectional study. Through simple random sampling, 157 adolescent girls were selected. Nutrition status was assessed using anthropometric measurements. Nutrient intake was collected using the food frequency questionnaire (FFQ). WHOQOL BREF was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 43 publications
0
2
0
1
Order By: Relevance
“…Misalnya, ketika seorang remaja ingin mengubah pola makannya ke pola makan yang lebih sehat, hal ini tidak dapat dicapai jika orang tua tidak dibekali dengan pengetahuan dan kemampuan yang sama untuk memberikan pilihan yang lebih sehat di rumah. Dalam situasi ini, sekolah juga berperan penting dalam menyediakan makanan dan jajanan serta minuman yang lebih sehat di lingkungan sekolah 7 .…”
Section: Pendahuluanunclassified
“…Misalnya, ketika seorang remaja ingin mengubah pola makannya ke pola makan yang lebih sehat, hal ini tidak dapat dicapai jika orang tua tidak dibekali dengan pengetahuan dan kemampuan yang sama untuk memberikan pilihan yang lebih sehat di rumah. Dalam situasi ini, sekolah juga berperan penting dalam menyediakan makanan dan jajanan serta minuman yang lebih sehat di lingkungan sekolah 7 .…”
Section: Pendahuluanunclassified
“…The recent Basic Health Survey demonstrated the poor eating pattern that is characterized by a low intake of vegetables and fruits group in almost all adolescents (95.5–98%) (Kementerian Kesehatan RI, 2018). Furthermore, although a study among adolescent girls in a rural area of Indonesia aged 15–19 years found low intake of micronutrients (vitamins and minerals) during the pandemic (Sari et al , 2022), eating patterns in adolescents living in an urban area is still limited. Adolescents with poor eating patterns are associated with a higher risk of hypertension (Tam et al , 2022).…”
Section: Introductionmentioning
confidence: 99%
“…The changes in parental lifestyle habits and their correlations with the changes in their children's diet during the first COVID-19 Lockdown in Greece were presented in the paper by Saltaouras et al [15] Evidence was also reported by Almazan et al [16] regarding the highest risk for Candida spp colonization in preschool Mexican aged children who adhered to a diet high in simple carbohydrates. Moreover, the manuscript by Sari et al offer important input about the association of nutrient intake and quality of life in girls living in a rural area in Indonesia, a population which is prone to malnutrition and poverty [17]. Finally, one systematic review summarized evidence about the role of family in the association between obesity and depression in children, reporting the lack of studies in this area, while one meta-analysis studied the effect of air pollution on childhood obesity and found strong evidence about its harmful effect on the risk of developing overweight or obesity in children [18,19].…”
mentioning
confidence: 99%